The Selective Politicization of Transatlantic Trade Negotiations - van Loon, Aukje (2020)
European Union (EU) trade policy is in the spotlight. The Transatlantic Trade and Investment Partnership (TTIP) negotiations triggered substantial public mobilization which emerged in a surge of literature on trade politicization. Notwithstanding politicization’s topicality and significance, it varies considerably over time, across trade agreements negotiations as well as across EU member states. By picking up on the latter, this article examines why, despite similar economic benefits potentially to be gained from trade liberalization, TTIP negotiations revealed striking differences in politicization in Germany and the UK. Understanding this variation is illustrated by highlighting the impact of some of TTIPs’ substantial issues mobilizing a range of materially and ideationally motivated stakeholders, who in turn shaped diverging governments’ trade positions of the countries under scrutiny. In explaining this selective politicization across two European countries, focus is on three explanatory variables, domestic material interests (business associations and trade unions), societal ideas (voters and non-governmental organizations [NGOs]) dominant in these countries’ domestic politics, as well as their interaction with national institutions. For this reason, the societal approach to governmental preference formation is employed which provides a detailed exploration of these three domestic factors, as well as the importance of their interdependence, in shaping the TTIP positions of the UK and German governments.